MTHFR promoter methylation might mitigate the effect of smoking at the level of LINE‐1 in cleft lip tissues: A preliminary study. Issue 20 (19th October 2021) - Khan, Mohammad Faisal J.; Little, Julian; Mossey, Peter A.; Butali, Azeez; Autelitano, Luca; Meazzini, Maria C.; Rubini, Michele
Abstract: Background: The medial and maxillary aspects of the upper lip originate at separate embryonic stages and therefore may experience different maternal exposure patterns which may affect methylation. Based on this hypothesis, we investigated the level of methylation of the methylene tetrahydrofolate reductase promoter gene (m MTHFR ) in tissues from cleft lip, and m MTHFR levels by MTHFR c.677C > T genotype. We further investigated whether m MTHFR mitigates the effect of smoking on long interspersed nuclear element (LINE‐1) methylation in these tissues. Methods: DNA extracted from medial and lateral tissues of 26 infants with nonsyndromic cleft lip with or without cleft palate (nsCL/P) was bisulfite converted and m MTHFR was measured on a pyrosequenser. LINE‐1 methylation and MTHFR c.677C > T genotype data were obtained in our previous study. Results: There was no substantial difference in m MTHFR ( p = .733) and LINE‐1 ( p = .148) between the two tissues. m MTHFR was not influenced by MTHFR c.677C > T genotype, but there was suggestive evidence that the difference was larger among infants exposed to maternal smoking compared to nonexposed. LINE‐1 methylation differences were significant ( p = .025) in infants born to nonsmoking mothers, but this was not apparent ( p = .872) in infants born to mothers who smoked. Our Pearson's correlation analysis suggested a weak inverse association between m MTHFR and LINE‐1 ( r = −.179, p = .381). Conclusion: Our preliminary observation of differences in patterns of m MTHFR levels in lip tissue suggests the interplay of gene and environment in the establishment of methylation in tissues at both sides of cleft lip. This requires investigation in a larger cohort, integrated with metabolic assessment.